Spectrophotometric Determination of Copper (II) by using Amoxicillin Drug as Reagent - Abbas Noor Alshirifi (Journal of Global Pharma Technology, 2017)
Trace amount of Copper was determined by spectrophotometric technique by using   amoxicillin-Sodium drug as new reagent.  Amoxicillin-Sodium reacted in highly basic solution at pH 11 with Copper (II) to give a violet colored product which has a maximum absorbance at wavelength 540 nm. The reaction was immediate and its observance remained stable above 1 an hour.   The molar absorptivity   was found to be 0.3 × 104  L mol-1 cm-1, Shandell's sensitivity was 2.08 ×10-1μg cm-2 . And the linearity of the calibration curve, which obeyed to beer's low limits was obtained for 5-32 µg mL-1of Cu (II). The stoichiometric composition of the colored   product   was 1: 1 [Copper: Amoxicillin-Sodium] by using Job’s method, mole ratio method and molar conductivity.The Limit of Detection (LOD) and limit of quantifications (LOQ) were calculated by using suitable equations, which were found to be 0.29 μg/mL-1 and 0.97µg/mL-1 respectively.Interferences    due to Fe (III), Co (II), Ni (II), Zn (II), Ag (I) were investigated. The method is high selectivity and used for determination of copper in samples.Keywords: Copper(II) ,Amoxicillin drug , Reagent.